2014
DOI: 10.5294/aqui.2014.14.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Nursing Students’ Research Activities and Utilization: A Turkish Sample

Abstract: Objective: The aim of this study was determine undergraduate nursing students' research activities and utilization. Method: A descriptive design was used in the study. This study conducted with undergraduate nursing students at the two universities in Turkey during the spring term of 2012. The population consisted of 216 participants. The data were collected through a questionnaire developed by the author based on literature. The Percentage, Chi-square and Fisher's exact tests were used to evaluate the collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
5

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
1
7
0
5
Order By: Relevance
“…The moderate positive significant relationship concerning age and both deep and surface learning approaches suggests that age has some influence on the increase and decrease of deep and surface learning approach scores. The finding is supported by earlier studies 31 , 32 using the R-SPQ-2F instrument, which similarly found a positive correlation between these variables. In contrast, the surface approach to learning is negatively correlated with age as measured using the R-SPQ-2F instrument.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The moderate positive significant relationship concerning age and both deep and surface learning approaches suggests that age has some influence on the increase and decrease of deep and surface learning approach scores. The finding is supported by earlier studies 31 , 32 using the R-SPQ-2F instrument, which similarly found a positive correlation between these variables. In contrast, the surface approach to learning is negatively correlated with age as measured using the R-SPQ-2F instrument.…”
Section: Discussionsupporting
confidence: 84%
“…26 It is essential to encourage groups to not only have a mix of different learners’ ages and diverse ways of effective learning but also to mix learners with interesting and positive attitudes towards learning. 32 While results suggest purposively mixing students to enhance deep approach learning, teachers should consciously and carefully select and develop group activities and dynamics that will empower students.…”
Section: Discussionmentioning
confidence: 99%
“…Embora ultimamente, a transferência do conhecimento para a clínica, tenha ganho notoriedade, os investigadores têm sido confrontados com desafios complexos, desde o desenho até a utilização dos resultados dos seus estudos, o que não possibilita a sua apropriação pela práxis (Cardoso et al, 2020;Cardoso et al, 2021). Nem também pelos estudantes de enfermagem, dado que 87% não usa os resultados da investigação na clínica e referem que a não utilização da evidência disponível relaciona-se com conhecimento insuficiente sobre a utilização da investigação (Ertug, & Önal, 2014).…”
Section: Discussionunclassified
“…Mevcut çalışmada da, herhangi bir araştırma etkinliğine katılma, (araştırma planlama ve uygulama aşamasına katılma) ve denek olarak araştırmalar da aktif rol alma durumlarının hemşirelikte araştırma dersi alan öğrenciler arasında dersi almayan öğrencilere kıyasla daha fazla olması araştırma dersinin pozitif etkisini göstermektedir. Ertuğ ve Önal (30) , araştırma eğitimi ve araştırma yürütme arasında anlamlı bir ilişki olduğunu araştırma dersi alan öğrencilerin almayanlara göre daha fazla araştırma etkinliğine katıldıklarını bildirmişlerdir. Erkin ve ark.…”
Section: Discussionunclassified